-6x+7+7x=6+x+1

Simple and best practice solution for -6x+7+7x=6+x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+7+7x=6+x+1 equation:


Simplifying
-6x + 7 + 7x = 6 + x + 1

Reorder the terms:
7 + -6x + 7x = 6 + x + 1

Combine like terms: -6x + 7x = 1x
7 + 1x = 6 + x + 1

Reorder the terms:
7 + 1x = 6 + 1 + x

Combine like terms: 6 + 1 = 7
7 + 1x = 7 + x

Add '-7' to each side of the equation.
7 + -7 + 1x = 7 + -7 + x

Combine like terms: 7 + -7 = 0
0 + 1x = 7 + -7 + x
1x = 7 + -7 + x

Combine like terms: 7 + -7 = 0
1x = 0 + x
1x = x

Solving
1x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1x + -1x = x + -1x

Combine like terms: 1x + -1x = 0
0 = x + -1x

Combine like terms: x + -1x = 0
0 = 0

Simplifying
0 = 0

The solution to this equation could not be determined.

See similar equations:

| .75(0)-.66x=12 | | ae+n=p | | 0=2x^2+9x+4 | | 6k-(5+k)=-(3k+5) | | 3x^4-6x^3-2x^2=0 | | 2y^2-9y+8=0 | | 6n-22=-18+5n | | 12x+7=12x-5 | | x-.12x=503.23 | | 3t-17=-47+8t | | -3x-7y=14 | | 3(x-4)+4x-7=-3x+11 | | 2(10)-y=14 | | 5.5+2x=41.5 | | 19.9x+10=34+9.9x | | 3x^2+12=20x | | p=60-3q | | x=5-3y | | Y+(y+1)+(y+2)=45 | | (3t-12)=27 | | a^3-8a=3 | | 6=10-4 | | 36=7b+1 | | 5x-7=(-6)x-29 | | 4x-2(x-5)=-3+4x+4 | | -p-2=18-27p+6 | | 1650+x(145.50)=3250.50 | | 22c+17=11+3c | | 10=0.3x+9.1 | | -9x-7(0)=-30 | | 2x^4-4x^3-1x^2=0 | | 6=-5x+21 |

Equations solver categories